Sporotrichosis by Sporothrix schenckii senso stricto with itraconazole resistance and terbinafine sensitivity observed in vitro and in vivo : case report - Vettorato, Rodrigo (2018)
We report a case of a patient with lymphocutaneous sporotrichosis in the right upper limb. The fungus was identified as Sporothrix schenckii senso stricto by calmodulin gene sequencing. The initial treatment was itraconazole (200 mg/day), but in vitro antifungal susceptibility demonstrated high resistant to this and another six antifungals, with exception to terbinafine. The lesions did not regress with itraconazole treatment. Thus, 500 mg/day of terbinafine was prescribed and clinical cure was obtained after four months.